Muscle Strength, Power, and Morphologic Adaptations After 6 Weeks of Compound vs. Complex Training in Healthy Men. - Stasinaki, Angeliki-Nikoletta; Gloumis, Giorgos; Spengos, Konstantinos; Blazevich, Anthony J; Zaras, Nikolaos; Georgiadis, Giorgos; Karampatsos, Giorgos; Terzis, Gerasimos (J Strength Cond Res, 2015)
The aim of the study was to compare the effects of compound vs. complex resistance training on strength, high-speed movement performance, and muscle composition. Eighteen young men completed compound (strength and power sessions on alternate days) or complex training (strength and power sets within a single session) 3 times per week for 6 weeks using bench press, leg press, Smith machine box squat, and jumping exercises. Pre- and posttraining, jumping and throwing performance and maximum bench press, leg press, and Smith machine box squat strength were evaluated. The architecture of vastus lateralis and gastrocnemius muscle was assessed using ultrasound imaging. Vastus lateralis morphology was assessed from muscle biopsies. Jumping (4 ± 3%) and throwing (9 ± 8%) performance increased only with compound training (p < 0.02). Bench press (5 vs. 18%), leg press (17 vs. 28%), and Smith machine box squat (27 vs. 35%) strength increased after both compound and complex training. Vastus lateralis thickness and fascicle angle and gastrocnemius fascicle angle were increased with both compound and complex training. Gastrocnemius fascicle length decreased only after complex training (-11.8 ± 9.4%, p = 0.006). Muscle fiber cross-sectional areas increased only after complex training (p ≤ 0.05). Fiber type composition was not affected by either intervention. These results suggest that short-term strength and power training on alternate days is more effective for enhancing lower-limb and whole-body power, whereas training on the same day may induce greater increases in strength and fiber hypertrophy.
Keywords: Adaptation, Physiological; Adult; Biopsy; Case-Control Studies; Humans; Male; Muscle Fibers, Skeletal; Muscle Strength; Muscle, Skeletal; Quadriceps Muscle; Resistance Training; Ultrasonography; Young Adult